The Ultimate small business marketing toolkit - Goldstein, Beth. (McGraw-Hill, 2008)
The Ultimate Small Business Marketing Toolkit gives you the resources to do just that, with a wide variety of cost-effective marketing techniques you can use to turn your business vision into reality.